Performance and Gaseous Emission Evaluation of Compression Ignition Engine using Palm Biodiesel Blend on Chassis Dynamometer - Palasai, Wasan; Kathiyawan, Taweesak; Srichai, Prathan (Princess of Naradhiwas University Journal, 2021)
This research presents the effects of palm biodiesel fuel efficiency and pollution. Palm was mixed with biodiesel by volume 7 (Commercial diesel) 20 40 60 and 100 percent. The maximum performances were measured such as horsepower and torque, brake specific fuel consumption to calculate the conversion of fuel into mechanical energy, thermal efficiency and measure gas pollution; Carbon Monoxide (CO), Carbon Dioxide (CO2), Hydrocarbons (HC), Oxygen (O2) and Nitrogen dioxide (NO2) of the car with the chassis dynamometer at a constant speed of 90 kilometers per hour and at the maximum open throttle at the test temperature conditions of 30-32 °C. From the experiments, the results revealed that the horsepower and torque tend to decrease with increasing biodiesel blend ratio, brake specific fuel consumption has increased, and the conversion of fuel into mechanical energy thermal efficiency has been decreased due to the reduced calorific value of the fuel as the high proportion of mixed biodiesel. In addition, the measurements of gas pollution such as Carbon Monoxide (CO), Carbon Dioxide (CO2), Hydrocarbons (HC) were decreased but nitrogen dioxide (NOx) tends to increase. This is due to the reduction of carbon content and the increase of oxygen.